The Use of English Song to Improve Student's Pronunciation in the Fourth Grade of SDN Pasekaran 02 Batang in 2009/2010 Academic YEar - MARTIANI, ADE IRMA (2011)
This research paper is aimed at describing the process of teaching pronunciation, describing the students' response toward the technique, and to know whether teaching pronunciation using an English song can improve the students' pronunciation in SD N Pasekaran 02 Batang. The researcher used Classroom Action Research (CAR). The data are quoted from the observation, test, and interview. The procedures of research are: planning, implementing, observing, and reflecting. To examine whether teaching pronunciation can improve students' pronunciation, the researcher gives some tests namely pre-test and posttest. Each test consists of 20 items. In pre-test the highest score is 65, the lowest score is 40, and mean score is 53. In cycle I the highest score is 73.4, the lowest score is 40, and the mean score is 54.69. In cycle II the highest score is 65, the lowest score is 53, and mean score is 52. While, in post-test the highest score is 100, the lowest score is 80, and the mean score is 89.75. It means that teaching pronunciation using English song could improve the students' pronunciation in short time.